Carotid Revascularization: Current Practice and Future Directions - Bagley, Jacob H.; Priest, Ryan (Seminars in Interventional Radiology, 2020)
Carotid stenosis is responsible for approximately 15% of ischemic strokes. Carotid revascularization significantly decreases patients' stroke risk. Carotid endarterectomy has first-line therapy for moderate-to-severe carotid stenosis after a series of pivotal randomized controlled trials were published almost 30 years ago. Revascularization with carotid stenting has become a popular and effective alternative in a select subpopulation of patients. We review the current state of the literature regarding revascularization indications, patient selection, advantages of each revascularization approach, timing of intervention, and emerging interventional techniques, such as transcarotid artery revascularization.
Keywords: carotid revascularization; carotid stenosis; carotid stent; carotid endarterectomy; transcarotid artery revascularization; interventional radiology